The R-word index for Switzerland - David Iselin; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2012)
In a pioneering attempt we present the R(ecession)-word index for Switzerland. We evaluate its predictive ability of GDP growth using real-time vintages of GDP data, closely simulating flow of information in the past. We find that inclusion of the R-word index led to statistically significant improvement in forecast accuracy over the benchmark autoregressive model. Largest improvements in forecast accuracy were observed in the period around the Great Recession.
Keywords: C22; C53; 330; Recession; nowcasting; real-time data; Switzerland; Konjunktur; Sozialprodukt; Prognoseverfahren; Schweiz